The environmental dependence of X-ray AGN activity at z ∼ 0.4. Issue 3 (7th September 2020) - Noordeh, E; Canning, R E A; King, A; Allen, S W; Mantz, A; Morris, R G; Ehlert, S; von der Linden, A; Brandt, W N; Luo, B; Xue, Y Q; Kelly, P
ABSTRACT: We present an analysis of the X-ray active galactic nucleus (AGN) population in a sample of seven massive galaxy clusters in the redshift range 0.35 < z < 0.45. We utilize high-quality Chandra X-ray imaging to robustly identify AGN and precisely determine cluster masses and centroids. Follow-up VIsible Multi-Object Spectrograph optical spectroscopy allows us to determine which AGN are cluster members. Studying the subset of AGN with 0.5–8 keV luminosities >6.8 × 10 42  erg s −1, within r ≤ 2 r 500 (approximately the virial radius), we find that the cluster AGN space density scales with cluster mass as $\sim M^{-2.0^{+0.8}_{-0.9}}$ . This result rules out zero mass dependence of the cluster X-ray AGN space density at the 2.5σ level. We compare our cluster X-ray AGN sample to a control field with identical selection and find that the cluster AGN fraction is significantly suppressed relative to the field when considering the brightest galaxies with V < 21.5. For fainter galaxies, this difference is not present. Comparing the X-ray hardness ratios of cluster member AGN to those in the control field, we find no evidence for enhanced X-ray obscuration of cluster member AGN. Lastly, we see tentative evidence that disturbed cluster environments may contribute to enhanced AGN activity.